The Differential Roles of T Cells in Non-alcoholic Fatty Liver Disease and Obesity - Van Herck, Mikhaïl A.; Weyler, Jonas; Kwanten, Wilhelmus J.; Dirinck, Eveline L.; De Winter, Benedicte Y.; Francque, Sven M.; Vonghia, Luisa (Frontiers in Immunology, 2019)
Non-alcoholic fatty liver disease (NAFLD) constitutes a spectrum of disease states characterized by hepatic steatosis and is closely associated to obesity and the metabolic syndrome. In non-alcoholic steatohepatitis (NASH), additionally, inflammatory changes and hepatocellular damage are present, representing a more severe condition, for which the treatment is an unmet medical need. Pathophysiologically, the immune system is one of the main drivers of NAFLD progression and other obesity-related comorbidities and both the innate and adaptive immune system are involved. T cells form the cellular component of the adaptive immune system and consist of multiple differentially active subsets, i.e. T helper (Th) cells, regulatory T (Treg) cells and cytotoxic T (Tc) cells, as well as several innate T-cell subsets. This review focuses on the role of these T-cell subsets in the pathogenesis of NAFLD, as well as the association to obesity and type 2 diabetes mellitus, reviewing the available evidence from both animal and human studies. Briefly, Th1, Th2, Th17 and Th22 cells seem to have an attenuating effect on adiposity. Th2, Th22 and Treg cells seem to decrease insulin resistance, whereas Th1, Th17 and Tc cells have an aggravating effect. Concerning NAFLD, both Th22 and Treg cells appear to have an overall tempering effect, whereas Th17 and Tc cells seem to induce more liver damage and fibrosis progression. The evidence regarding the role of the innate T-cell subsets is more controversial and warrants further exploration.